A RARE PRESENTATION OF MULTIPLE HYDATID CYSTON EITHER SIDE OF DIAPHRAGM - Rana Tabassum Ansari et al (Baqai Journal of Health Sciences)
Cystic echinococcosis (CE) or more commonly known as hydatid cyst is a zoonotic infection caused by Echinococcus granulosus. Although the two most common locations of hydatid cyst are liver and lungs, it may appear in any other part of the body and therefore clinical presentation of the infection largely depends on the site and size of the lesion. In the present study, a 65 years old Afghan ex-smoker male diagnosed with tuberculosis was presented with the symptoms such as cough, hemoptysis, chest pain, shortness of breath on exertion and low-grade fever. The antituberculous treatment was stopped with no benefit and then the patient was treated with albendazole at a dose of 15 mg/kg/day in divided doses for three months. The treatment was stopped at three months time with a 14 days drug-free period following which the treatment was restarted. The treatment continued for three cycles each lasting for three months with a 14 days drug-free period. The patient treated with albendazole was discharged in healthy condition. However, surgical resection of cysts is another safe alternative to avoid the rupture and consequent anaphylaxis